Primary cubital tunnel syndrome – surgical treatment methods and their effectiveness - Starownik, Jakub; Szewczyk, Artur; Kołpaczyńska, Sylwia; Niedobylski, Sylwiusz; Bartoszek, Lidia; Orłowska, Dominika; Wójcik, Aleksandra (Quality in Sport, 2024)
Cubital tunnel syndrome (CuTS) is one of the most common neuropathies of the upper extremity. This condition, if left untreated, can significantly impact patients' everyday functioning and quality of life. Diagnosis of CuTS is mostly based on clinical evaluation but can be supplemented by electrodiagnostic studies, and various imaging techniques. Conservative treatments such as physical therapy, splinting, and anti-inflammatory medications are often first-line interventions. However, surgical approach may become necessary when conservative measures fail to provide relief or in cases of severe compression. There are numerous surgical approaches to treating CuTS and there is no clear consensus on one best method. Simple decompression of the ulnar nerve and its subcutaneous transposition are the most popular surgical techniques employed. Each method has its advantages and drawbacks, with varying implications for nerve recovery and postoperative complications. This review aims to provide a comprehensive overview of CuTS, while focusing on available surgical treatment approaches, their popularity and outcomes. Further research is warranted to refine surgical techniques and develop more effective interventions for this debilitating condition.